Expert System for Diagnosis of Inflammatory Bowel Disease Using The Web Based Naive Bayes Method - Muhatri; Rida Utami (Jurnal Mantik, 2020)
This research aims to develop the world of computer technology, especially in the health sector. Inflammation of the intestine is a disease of the digestive tract in human organs and can occur at any age, but which often occurs at the age of 15-30 years. Inflammatory bowel disease or inflammatory bowel disease consists of 3 types, namely ulcerative colitis, pancolitis and Crohn's disease, where each type of disease has different symptoms. This study uses an expert system with the naïve Bayes method in determining solutions based on the symptoms experienced by the sufferer. The exact cause of intestinal inflammation is not known with certainty, but it is thought to be related to an immune system disorder in the human body. The main symptoms of inflammation of the intestine vary, depending on the location of the inflammation in the digestive tract. It is hoped that this web-based expert system for diagnosing inflammatory bowel disease will help facilitate the community in handling and solutions if they experience inflammatory bowel disorders independently.